Islamisasi Ilmu Pengetahuan Sosial: Panduan Al-Qur'An Dan Hadits Dalam Pengembangan Disiplin Ilmu Sosial - Asmar Sholeh; Ihdatul Wardah Caniago; Wanda Amelia Purba; Laila Khairani Nasution; Cahaya Indra; Heppy Ariani Harahap; Lailatun Nur Kamalia Siregar (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research discusses the development of social studies material at MIS Aisyiyah North Sumatra by integrating the teachings of the Koran and Hadith. Involving critical analysis of existing materials, this research sets out development steps that ensure alignment with Islamic principles. Methods include identification of material, assessment according to Islamic values, and preparation of new material. Teacher and stakeholder participation is integrated to ensure acceptance and effectiveness of implementation in the educational environment. This research is expected to provide practical guidance for MIS Aisyiyah and similar madrasas, enabling the development of social studies material that reflects Islamic values, strengthening students' understanding of social studies while strengthening the moral and spiritual foundation.